Professional baseball players demonstrate superior dynamic visual acuity and differences in vestibulo-ocular reflex performance, compared to similarly aged healthy controls - Filippini, T.; Kittelson, A.; Wagner, A.; Moody, V.; Schubert, M.; Loyd, B. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Baseball-specific movement paradigms require heightened ocular performance driven by the vestibular system. Normative data of vestibulo-ocular measures for high-level athlete populations is limited in the current literature, particularly under game-like conditions. This comparative cross-sectional study explores the vestibulo-ocular performance of professional baseball players, relative to healthy controls.